An integrated approach of 4G LTE and DSRC (IEEE 802.11p) for Internet of Vehicles (IoV) by using a novel cluster-based efficient radio interface selection algorithm to improve Vehicular Network (VN) performance - Hussain, Shaik Mazhar (Springer Science and Business Media Deutschland GmbH, 2022)
Internet of Vehicles (IoV) is a distributed network supporting V2X communications. Two potential technologies of V2X communications are dedicated short-range communication (DSRC) and cellular network technologies. DSRC provides low latency with direct connectivity to connect vehicles in a distributed manner. However, it suffers from reliability and serious link degradation problems. In contrast, cellular network offers high capacity, wider cell coverage range but suffers from high latencies due to long transmission time intervals. Hence, cellular networks limit their ability to support low-latency V2V communications, jeopardizing the effectiveness of safety applications. Hence, considering the above issues, single technology might not suffice the requirements of V2X applications under varying vehicle density scenarios. Therefore, for efficient V2X communications, it is required to interwork with DSRC and cellular technologies. Most of the existing solutions were based on either DSRC alone or cellular networks alone. Very few research works evaluated the performance of vehicular networks using hybrid approach. This paper reviews potential DSRC and wireless integrated solutions for efficient vehicular communications. Secondly, we highlight the limitations of each supporting vehicular communications. Then, we provide brief comparative analysis of each paper. Finally, we propose our algorithm to integrate DSRC and 4G LTE with novel optimal clustering-based data forwarding protocol for efficient data transmission in IoV. The performance of the proposed algorithm is evaluated in terms of end-to-end delay and throughput and compared with the existing approaches using NS-3 simulation tool.